New B-Z Oscillating Reactions Involving a Tetraazamacrocyclic Nickel(II) Complex - Hu, Gang; Xu, Zhi-qiang; Xie, Fu-Xing; Hu, Lin; Ni, Shi-Sheng (Asian Journal of Chemistry, 2010)
New Belousov-Zhabotinskii reactions using a tetraazamacrocyclic nickel complex as catalyst in NaBrO3-pyruvic acid-H2SO4 system have been investigated. This complex contains unsaturated macrocyclic ligand 11,13- dimethyl-1,4, 7,10-tetraazacyclotrideca-1, 10, 12-triene. The concentration oscillations of this system are damped rapidly due to the consumption of the catalyst. Acrylonitrile, H2O2, vitamin C, glucose or CCl4 present in the system can inhibit the oscillations. Unlike the classical B-Z oscillating system, variations in the initial concentrations of the components markedly affect the potentiometric oscillation parameters and the shapes of the oscillations.